High-mobility group box 1 expression in mandibular bone cells of experimental periodontitis - Yuliana Mahdiyah Da'at Arina; Mohamad Rubianto; F Ferdiansyah; I Ketut Sudiana; Retno Pudji Rahayu; Hari Basuki Notobroto (Wolters Kluwer Medknow Publications, 2019)
Background: High-mobility group box 1 (HMGB1) was suggested to be associated with the pathogenesis of chronic periodontitis which characterized by alveolar bone loss. HMGB1 was defined as a bone-active cytokine, but the rule of HMGB1 in bone loss of chronic periodontitis is still understood. Aim: The aim of this study is to investigate the expression of HMGB1 on osteoblasts and osteoclasts in the mandible of chronic periodontitis. Methods: This experimental study was conducted to rats injected by Porphyromonas gingivalis into the buccal and lingual subgingival area at a concentration of 2 × 109 CFU/mL three times a week with 2-day apart for 2, 3, 4, and 6 weeks as chronic periodontitis group and injected by normal saline as control group. Analysis of variance was used to examine the differences between groups followed by least significant difference post hoc test with the level of significance was <0.05. Results: The HMGB1 expression was found in both osteoclasts and osteoblasts of mandibular bone by immunohistochemistry analysis. There was a difference of HMGB1 expression on osteoblasts and osteoclasts of chronic periodontitis. HMGB1 expression was found increased significantly in mandibular osteoblasts of chronic periodontitis, whereas the HMGB1 expression in mandibular osteoclast is higher in 2 and 3 weeks, but it was lower in 4 and 6 weeks. Conclusions: This study indicated a potential role for HMGB1 in bone loss of chronic periodontitis. HMGB1 on mandibular osteoclasts and osteoblasts may play different rules in the onset and progression of chronic periodontitis.